Perception and use of social media by Indonesian adolescents and parents: A qualitative study - Purboningsih, Eka Riyanti; Massar, Karlijn; Hinduan, Zahrotur Rusyda; Agustiani, Hendriati; Ruiter, Robert A. C.; Verduyn, Philippe (Frontiers in Psychology, 2023)
Social media are popular among adolescents worldwide, including the global South. The way adolescents use social media is influenced by their own perception of social media but also by how their parents use and perceive social media. This study aims to understand how Indonesian young adolescents (12–15 years old) and parents of adolescents use and perceive social media. For this purpose, we conducted eight focus group discussions and eight semi-structured interviews with 30 Indonesian adolescents and 15 Indonesian parents. Thematic analysis of the qualitative data reveals that both adolescents and parents use social media for social, practical, and pleasure activities. Most adolescents mention that they consider themselves skilled in using social media, while parents consider themselves less skilled. Both adolescents and parents mention that social media offer benefits for adolescents, including emotional, social, and practical benefits. However, adolescents and parents also mention the risks of social media use for adolescents, including social, emotional, and informational risks, as well as the displacement of more meaningful activities. As such, both adolescents and parents do not perceive social media as inherently good or bad but rather as a novel medium that offers benefits for adolescents but also involves several risks to be considered by parents and other relevant stakeholders. This study adds to our understanding of social media use in the global South and offers a theoretical basis for future studies on the impact of adolescents’ social media usage on wellbeing in an Indonesian context. However, future research is necessary to depict possible differences in social media use between Indonesia and other countries in the global South.